Evaluation and Calibration of Computerized Attitude Toward Physics Test : A Factor Analysis and Item Response Theory - Mafudi*, Innal; Kuswanto, Heru; Jumadi, Jumadi; Kurniawan, Aris; Fatmawati, Intan; Syar, Nur Inayah (Jurnal IPA & Pembelajaran IPA, 2025)
Attitude towards physics is one of the key factors in determining the success of physics learning. The solution to ensure a positive attitude towards physics requires a good diagnostic instrument. This study aims to develop an instrument that can measure attitudes toward physics validly and reliably. This study was conducted by validating the instrument with 8 experts physics education. Validation data was analysed using the Vaiken formula a score of 0.90 was obtained, which means that all items are valid. After the validation stage, the instrument was tested on 423 respondents consisting of high school students from the provinces of East Java and Riau. The test data were analysed through four steps: 1) exploratory factor analysis, 2) confirmatory factor analysis, 3) Cronbach's alpha reliability, and 3) item response theory using the graded response model. The EFA results showed that from 16 question items, they resulted in groupings into 4 factors: Teacher and Physics as a Future Vocation, Physics learning, Physics as a Process, and Enthusiasm toward Physics. The reliability of the items based on cronbach's alpha score 0.94 category a very good reliability level. The performance of each item through the IRT GRM analysis shows that the item discrimination power is in the moderate to very high category, and the item support is in the easy to moderate category. The CATP test is feasible and reliable in measuring attitudes toward physics